Imaging of Post Transthoracic Needle Biopsy Complications. Issue 2 (May 2019) - Dubé, Jean-Philippe; Azzi, Ziad; Semionov, Alexandre; Sayegh, Karl; Kosiuk, John; Pressacco, Josephine
When faced with characterization of a suspicious lung lesion, transthoracic needle biopsy (TTNB) is the standard technique used to retrieve a pathological specimen. Usual complications reported for this intervention are pneumothorax, hemorrhage, air embolism, and tumor seeding. This pictorial essay illustrates imaging of these complications.